PENGARUH PEMBERIAN PUPUK UREA DAN PUPUK MAJEMUK SUPER VIT DIAMOND TERHADAP PERTUMBUHAN DAN PRDOUKSI TANAMAN KACANG TANAH (Arachis hypogeae L.) - Yudi Triyanto (UNIVERSITAS LABUHANBATU, 2019)
The aim of this research is to know the effect of urea fertilizer and the appropriate Super-Vit fertilizer in order to obtain good peanut plant growth and to see whether there is a real interaction between the two factors on the growth of peanut plant. This research was conducted at Jl. Dewi Sartika Gg. Education. South Rantau District Labuhanbatu Regency of North Sumatra Province, with an altitude of ± 54 M from sea level. The method used is Factorial Random Design (RAK) Factorial with 12 treatment combinations and 3 replications, Urea fertilizer factor Consisting of 4 levels: U0 = 0 gr / plant, U1 = 1 gr / plant, U2 = 2 gr / plant, U3 = 3 gr / plant, while Super-Vit fertilizer factor consists of 3 levels ie: S0 = 0 gr / Plant, S1 = 0.2 gr / plant, S2 = 0.3 gr / plant. Parameters observed were 4, ie plant height, number of pods per sample plant, weight of 1000 seeds, and production amount per plot. The treatment of urea fertilizer had no significant effect on plant height parameter and weight of 1000 seeds, while the effect was very real on the number of pods containing the plant and the amount of production per plot, the treatment of Super-Vit fertilizer showed a significant effect on the parameters of plant height, Pod containing per plant sample, and production amount per plot. But no significant effect on weight parameter of 1000 grain seeds. Treatment of interaction between Urea fertilizer and Super-Vit fertilizer showed no significant effect on plant height parameters, number of pods per sample plant, weight of 1000 seeds, and production amount per plot. Keywords: peanut, compound fertilizer, urea fertilizer.